Properties of a Subclass of Avakumović Functions and Their Generalized Inverses - Buldygin, V. V.; Klesov, O. I.; Steinebach, J. G. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We study properties of a subclass of ORV functions introduced by Avakumović and provide their applications for the strong law of large numbers for renewal processes.